Researchers journey in conducting interview on breastfeeding experience among Malay mother - Muda, Siti Mariam; Jamil, Nurul Akma (IIUM Press, 2018)
In Malaysia, breastfeeding was dominantly practiced among Malay whose deeply believe in Islam and any decision should abide by Islamic teachings. Existing literature appear to have limited evidence on Malay mothers’ interpretation and construction of this practice. The decision to breastfeed was believed to be influenced by social and cultural context. Therefore, in order to explore life experience of breastfeeding mothers on their beliefs related to religious and sociocultural, qualitative study design was used. A minimal guidance of phenomenological approach adopted as the methodological framework. Semi structured interviews were carried out among 15 mothers whose were recruited from four Maternal and Child Health Clinic in Kuantan using purposive sampling. The experience of researchers thorough out their journey will be shared in terms of challenges; barriers and solution to overcome the concerned that exist while conducting in-depth interview session.